Remediation of soil contaminated with a commercial diesel-biodiesel blend (B12): A microcosm evaluation on the effects of (in)organic amendments. (January 2022) - Della-Flora, Isabela Karina; Clerici, Naiara Jacinta; Dupont, Gabriele Kuhn; Serafini, Carolina Grings; Daroit, Daniel Joner
Abstract: Bioremediation of fuel-contaminated soils largely depends on microbial activities, which might be stimulated using (in)organic amendments. Attenuation of a diesel-biodiesel blend (B12) was investigated in microcosms during 93 days. Soil was spiked with B12 (5%, m m −1 ) and, in addition to contaminated Controls (unamended), soils received compost (COB), soybean hulls (SHB), or NPK fertilizer (IB) to reach a ~20:1 carbon-to-nitrogen (C:N) ratio regarding B12-carbon content. Effects of treatments on B12 attenuation, soil respiration, heterotrophic and B12-utilizing bacteria, pH, organic-C, nitrogen contents, and phytotoxicity, were evaluated. After 20 days, diesel range organics analysis indicated 58, 48, 45, and 43% attenuation in Controls, SHB, IB, and COB, respectively. Final dissipation reached 90, 86, 72, and 60% in Controls, COB, IB, and SHB. Compost and soybean hulls appeared as preferential substrates for microorganisms. Although microbial activity (soil respiration) was 39 and 22% higher than Controls in COB and SHB, amendments postponed attenuation. Amendments transiently affected bacterial numbers as compared to Controls; however, these effects were not related to attenuation levels. pH of the contaminated soils (~7.0) dropped to 6.1 in IB, whereas pH values were between 6.7 and 7.6 in other treatments. Organic-N and Kjeldahl-N decreased during incubations, indicating net N mineralization and subsequent nitrification, although N losses could occur. Organic-C, initially higher in SHB and COB, decreased in all treatments; however, more prominent losses in COB and SHB suggest amendments were preferentially used by microorganisms. Phytotoxicity was improved in Controls; however, it was not associated with attenuation levels in amended treatments, possibly owing to formation of toxic products and B12 sorption/desorption. In IB, decreased microbial activity, delayed attenuation, and remarkable phytotoxicity were due to excessive fertilization. Therefore, intrinsic soil conditions were adequate for B12 attenuation, without the need for nutritional inputs. Results also demonstrate that toxicity bioindicators are relevant to monitor remediation. Highlights: Adding compost and soybean hulls to B12-spiked soil enhanced microbial activity. Increased microbial activity was not translated into higher fuel dissipation. Inorganic fertilization (NPK) depressed microbial activity and fuel attenuation. Higher fuel dissipation was not necessarily related with a decreased phytotoxicity. Overall, unamended soil showed best results regarding attenuation and phytotoxicity.